ESTIMASI MATEMATIS UNTUK JUMLAH PENGIRIMAN PAKET BARANG DI JNE MOJOKERTO DENGAN METODE DOUBLE EXPONENTIAL SMOOTHING - Dwi Roudhotillah; Vita Kusumasari; Mochammad Hafiizh; Imam Supeno (UNIVERSITAS NEGERI MALANG, 2021)
The increasing number of package shipments of goods at JNE Mojokerto could highly affect the delays in time delivery. It is strongly necessary to mathematically estimate the number of package shipments of goods for the next month to prepare the resources that are needed by the company. The estimated number of deliveries is calculated by applying the Double Exponential Smoothing method. The monthly data obtained from January 2017 until December 2019 are used in that method, while the 4 months data from January 2020 until April 2020 are used to validated the estimation results. This result shows that the estimation for 4 months from January 2020 until April 2020 are 86421, 87787, 89154, and 90520 respectively. From the validation, the mean absolute percentage error 8%.